Afterglow, TL and OSL properties of Mn2+-doped ZnGa2O4 phosphor - Luchechko, Andriy; Zhydachevskyy, Yaroslav; Ubizskii, Sergii; Kravets, Oleh; Popov, Anatoli I.; Rogulis, Uldis; Elsts, Edgars; Suchocki, Andrzej; Bulur, Enver (Nature Publishing Group, 2019)
Zinc gallate (ZnGa2O4) spinel ceramics doped with Mn2+ ions was prepared by a solid-state reaction at 1200 °C in air. Manganese concentration was equal to 0.05 mol.% of MnO with respect to ZnO. Ceramics produced in this way show an efficient green emission at about 505 nm under UV or X-ray excitations, which is caused by Mn2+ ions. This green emission is observed also as a relatively long afterglow (visible to the naked eye in the dark for about one hour) after switching-off the X-ray excitation. Time profiles of the beginning of glow and afterglow have been studied together with thermally stimulated (TSL) and optically stimulated (OSL) luminescence. Experimental results demonstrate a presence of few types of shallow and deep traps responsible for the observed afterglow and TSL/OSL emission of the material. The possibility of pulsed optical stimulation and time-resolved OSL characteristics of ZnGa2 O4: Mn2+ has been reported for the first time. The presented results suggest the ZnGa2O4: Mn2+ spinel as a promising material for further fundamental research and possibility of application as a green long-lasting phosphor or storage phosphor for TSL/OSL radiation dosimetry.
The work was supported by Latvian Research Council via LZP-2018/1–0214 research project as well as the Latvian-Ukrainian Joint Research Project (LV-UA/2016/1 in Latvia and M/8-2018 (No. 0118U001672) in Ukraine), and by the NATO SfP Project G4649. The work was also partially supported by the Polish National Science Center (project 2018/31/B/ST8/00774). A. Luchechko gratefully acknowledges a grant from Institute of Physics PAS for a research visit to the Institute.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics